Fetal Hemivertebra at 11 to 14 Weeks' Gestation. (15th April 2020) - Yulia, Angela; Pawar, Sona; Chelemen, Oana; Ushakov, Fred; Pandya, Pranav P.
Abstract : Hemivertebra appears as an angulation of the spine on a coronal section. We evaluated the prevalence of chromosomal defects and outcome of fetuses with hemivertebra detected in the first trimester over a 9‐year period in a single tertiary referral unit. There were 10 cases; 9 had other anomalies. Seven couples opted for termination of pregnancy. One pregnancy ended in fetal demise at 16 weeks, and the 2 isolated cases continued the pregnancy with delivery at term. A karyotype analysis was performed in 8 fetuses: 5 found to be euploid and 3 having trisomy 18. Comprehensive ultrasound screening allows early prenatal detection and appropriate counseling.